Dependence of Temperature and Time during Heating of Tungsten Carbide-Based Hard Alloy Powders (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The physico-mechanical and operational properties of hard alloys produced for various industries depend on many factors, the main of which are: production technology, physico-chemical composition of binding additives, size of carbide powders, cooking and cooling processes, level of internal stresses in phase components, structure of alloys.